Comparative Analysis of Calculation of Income Tax Article 21 and Zakat - Tutut Adiningsih; Ronan Roby Cahyandi (AL- IKTISAB Journal of Islamic Economic Law, 2019)
The purpose of this paper is to examine the comparison of Article 21 Income Tax calculations using the gross method, the net method, and the gross-up method to find out which method is most profitable for company profits. This study uses similar comparisons that were made for the calculation of zakat, which also used 2 (two) methods, namely the net and gross methods. Data on employee salaries used in this study are secondary data obtained from PT. Sinar Abadi Pratama Sejahtera in 2018. The analytical method used in this study is a descriptive analysis with a qualitative approach. The findings in this study are to show that of the three methods of calculating Article 21 Income Tax, the most significant profit is the gross-up method. As for the calculation of zakat, which is beneficial for zakat payers is to use the net method. Calculation of Income Tax Article 21 gross-up method, produces the smallest corporate income tax while still meeting the tax requirements. Employees enjoy the benefits of receiving income tax benefits so that they can receive a full salary. On the net zakat calculation method, the zakat calculation is smaller than if using the gross method.